ADAPTATION OF THE ADDICTION TEST ON SOCIAL MEDIA - Makarevičs, Valērijs; Iliško, Dzintra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The issue of addiction to social networks is relevant for our time. The studies carried out in different cultural contexts indicate that addicted people are anxious, less satisfied with life, they may have problems with academic performance and with the achievement of their life and professional goals. Addicted people are more common among younger generation. For the diagnostic and corrective work with people who have addiction problems, require appropriate tools. One of these tools is described in our work. This is a test of dependence by Sheinov in addiction on social networks. The purpose of this study was to translate this test into the Latvian language, to check its reliability and validity. The relevant procedures described in the text of the article indicate to a high degree of reliability and validity of this test. It can also be used for the scientific purposes.